ANALISIS KESALAHAN DALAM MENYELESAIKAN SOAL MATEMATIKA BERDASARKAN NEWMAN’S ERROR ANALYSIS (NEA) PESERTA DIDIK DI KELAS IX SMP NEGERI 20 PADANG - Irviony, Tiara (Departemen Matematika, 2023)
Achievement of learning mathematics can be seen through evaluation. However, the results of the evaluation in class IX of SMP Negeri 20 Padang are still low. This is because students make mistakes in solving questions. Therefore, an analysis of these errors was carried out to measure the quality of student answers. One solution to measure the quality of students' answers is by using error analysis based on Newman's Error Analysis (NEA). The errors studied were based on indicators of Newman's errors. This type of research is descriptive with research subjects as many as ten class IX students of SMPN 20 Padang. The results showed that the research subjects tended to make (a) mistakes in reading the questions in the form of mistakes in reading the important information in the questions and not using that information to solve the problems; (b) problem transformation errors in the form of not being able to transform the questions into patterns and sequences or being able to find patterns in the questions, but are wrong; (c) problem transformation errors in the form of not being able to transform the questions into patterns and sequences or being able to find patterns in the questions, but are wrong; (d) Errors in writing the final answer in the form of not writing down the answer, making a mistake at the previous stage or not completing the calculation according to what the question asked for.Keywords– Error Analysis, Newman Error Analysis, Mathematics